2016
DOI: 10.1002/mpr.1552
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the structure of the CAST (Cannabis Abuse Screening Test) in 13 European countries using multigroup analyses

Abstract: Our aims are to describe and explain the structure of the Cannabis Abuse Screening Test (CAST) across countries. Standard statistical analyses fail to describe and explain several variables simultaneously while taking account of the group structure of individuals. The 2011 European School Survey Project on Alcohol and other Drugs (ESPAD): 5204 last-year cannabis users aged 15-16 from 13 European countries. Multigroup principal component analysis (mgPCA) and multigroup partial least squares (mgPLS). MgPCA shows… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 35 publications
0
2
1
Order By: Relevance
“…The indicators of the CAST internal consistency obtained were high and exceeded those obtained in some prior studies (Bastiani et al, 2013;Legleye et al, 2012;Legleye et al, 2011). Most studies had suggested a unidimensional structure of the CAST (Bastiani et al, 2013;Fernandez-Artamendi et al, 2012;Gyepesi et al, 2014), yet other studies suggested a bidimensional CAST model (Cuenca-Royo et al, 2012;Legleye, Eslami, & Bougeard, 2017). In our study, the confirmatory factorial analysis with one and two factors in both versions of the tool (CAST-f and CASTb) revealed that the goodness-of-fit indicators of the two-factor model are slightly better than those of the one-factor model.…”
Section: Discussioncontrasting
confidence: 61%
“…The indicators of the CAST internal consistency obtained were high and exceeded those obtained in some prior studies (Bastiani et al, 2013;Legleye et al, 2012;Legleye et al, 2011). Most studies had suggested a unidimensional structure of the CAST (Bastiani et al, 2013;Fernandez-Artamendi et al, 2012;Gyepesi et al, 2014), yet other studies suggested a bidimensional CAST model (Cuenca-Royo et al, 2012;Legleye, Eslami, & Bougeard, 2017). In our study, the confirmatory factorial analysis with one and two factors in both versions of the tool (CAST-f and CASTb) revealed that the goodness-of-fit indicators of the two-factor model are slightly better than those of the one-factor model.…”
Section: Discussioncontrasting
confidence: 61%
“…While the scales were never previously compared directly in the same sample, some previous studies conducted in adolescent samples found that the CUDIT‐R performed better in terms of sensitivity (0.93) than specificity (0.70) [12]. By contrast, the full CAST appeared generally slightly more specific than sensitive when the recommended cut‐off is applied [13,14], although this ratio can be adjusted by using lower thresholds [15]. These findings mean that in this population the CAST identifies more people with CUD, but at the cost of more false positives, compared to the CUDIT‐R‐Fr, based on the initial cut‐offs.…”
Section: Discussionmentioning
confidence: 96%
“…Good psychometric properties (e.g., high internal consistency) of both versions have been reported [48,49]. Satisfactory cross-cultural adaptation has been also documented [50,51]. In a sample of Italian young adults, using the Multiple Correspondence Analysis (MCA), Bastiani et al [40] maximized item homogeneity of the CAST and obtained the best score in relation to the importance of the response categories for each item.…”
Section: Self-report Measuresmentioning
confidence: 99%